Physiological and image-based phenotyping assessment of waterlogging responses of three kiwifruit rootstocks and grafting combinations - Calabritto, Maria; Mininni, Alba N.; Di Biase, Roberto; Petrozza, Angelo; Summerer, Stephan; Cellini, Francesco; Dichio, Bartolomeo (Frontiers in plant science, 2025)
Kiwifruit species have a relatively high rate of root oxygen consumption, making them very vulnerable to low root zone oxygen concentrations resulting from soil waterlogging. Recently, kiwifruit rootstocks have been increasingly used to improve biotic and abiotic stress tolerance and crop performance under adverse conditions. The aim of the present study was to evaluate morpho-physiological changes in kiwifruit rootstocks and grafting combinations under short-term waterlogging stress. A pot trial was conducted at the ALSIA PhenoLab, part of the Phen-Italy infrastructures, using non-destructive RGB and NIR image-based analysis and physiological measurements to identify waterlogging stress indicators and more tolerant genotypes. Three pot-grown kiwifruit rootstocks ('Bounty 71,' -B; 'D1,' var. -D; and 'Hayward,' var. -H) and grafting combinations, with a yellow-fleshed kiwifruit cultivar ('Zesy 002,' var. ) grafted on each rootstock (Z/B, Z/D, Z/H), were subjected to a control irrigation treatment (WW), restoring their daily water consumption, and to a 9-day waterlogging stress (WL), based on substrate saturation. Leaf gas exchange, photosynthetic activity, leaf temperature, RGB, and NIR data were collected during waterlogging stress. Stomatal conductance and transpiration reached very low values (less than 0.05 mol m s and 1 mmol m s , respectively) in both waterlogged D and H rootstocks and their grafting combinations. In turn, leaf temperature was significantly increased and photosynthesis was reduced (1-6 μmol m s ) from the first days of waterlogging stress compared to B rootstock and combination. The B rootstock showed prolonged leaf gas exchange and photosynthetic activity, indicating that it can cope with short-term and temporary waterlogging and improve the tolerance of grafted kiwi vines, which showed a decrease in stomatal conductance 5 days after the onset of stress. Morphometric and colorimetric parameters from the image-based analysis confirmed the greater susceptibility of D and H rootstocks and their grafting combinations to waterlogging stress compared to B. The results presented confirm the role of physiological measurements and enhance that of RGB and NIR images in detecting the occurrence of water stress and identifying more tolerant genotypes in kiwifruit.